HUMAN RIGHTS IN CRIMINAL PROCEEDINGS: CONCEPTUAL BASE AND LEGAL REGULATION - Tarasiuk, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the essence of human rights and to analyse the legal mechanisms for their enforcement in criminal proceedings, taking into account current challenges and international human rights standards. Research methods: to achieve this goal, the author used general scientific and special methods, in particular: methods of formal logic, comparative legal, systemic and structural, historical, formal legal methods, etc. Results: the article analyses the content of the concept of «human rights», identifies the main scientific approaches to understanding this concept, and highlights the legal nature of human rights, the problems affecting human rights and freedoms in connection with military aggression against Ukraine, and the specifics of human rights implementation in criminal proceedings. The author distinguishes scientific and doctrinal approaches to understanding the nature of human rights in criminal proceedings, focuses on the liberal and socio-legal approaches to human rights in criminal proceedings, and establishes that such constitutional human rights as the right to respect for dignity, the right to liberty and security of person, inviolability of the home, and the right to own, use and dispose of property are fundamental elements of the legal system which play a particularly important role in criminal proceedings, and therefore they should be. The author proves the need for a deeper understanding of the relationship between human rights, their realization and protection in criminal proceedings, as well as the need to develop scientific approaches to improving criminal procedure legislation in accordance with international human rights standards. The author emphasizes the importance of ensuring procedural guarantees in criminal proceedings, as well as the need to improve legal regulation to prevent arbitrary restrictions on the rights of participants to criminal proceedings.